Antimicrobials profiling, biofilm formation, and clonal lineage of methicillin-resistant Staphylococcus aureus isolated from cockroaches - Yasin Saberi; Mehrdad Halaji; Mohsen Karami; Jalal Jafarzadeh; Kasra Javadi; Hoda Shirafkan; Abazar Pournajaf (Heliyon)
Cockroaches are widely recognized as vectors for transmitting pathogenic microorganisms in hospital and community environments due to their movement between contaminated and human-occupied spaces. Staphylococcus aureus (S. aureus), particularly methicillin-resistant Staphylococcus aureus (MRSA), is a primary global health concern because of its capacity to cause a wide range of infections and its resistance to many antibiotics. Despite efforts to control nosocomial infections, the role of cockroaches in disseminating antibiotic-resistant bacteria has not been fully explored. This study aims to investigate the antibiotic resistance patterns, biofilm formation, and genetic characteristics of S. aureus isolated from cockroaches in hospital environments. Understanding the role of cockroaches as vectors of drug-resistant S. aureus can contribute to developing more effective infection control strategies in healthcare settings. This study examined 386 cockroaches, including 230 American and 156 German cockroaches. Antibiotic sensitivity, inducible resistance, and biofilm formation were evaluated. The presence of mecA, ermA, ermB, ermC, msrA, icaA, icaB, icaC, icaD, SCCmec, mupA, mupB, and iles-1 genes was determined. Randomly amplified polymorphic DNA typing was performed to determine genetic relatedness. Fifty S. aureus isolates were identified, with 48 % confirmed as MRSA. No isolate exhibited constitutive resistance to clindamycin. However, 96 % of the isolates displayed inducible clindamycin resistance (iMLSB phenotype) when tested using the D-test. The prevalence of icaA, icaB, icaC, and icaD genes were 34 %, 8 %, 0 %, and 0 %, respectively. So, 29.1 %, 16.6 %, 12.5 %, and 8.3 % of isolates had SCCmec gene cassettes of types I, II, III, and IV, respectively. The prevalence of ermA, ermB, ermC, and msrA genes was found to be 18 %, 16 %, 58 %, and 4 %, respectively. Seven different clusters were found in the RAPD-PCR, with cluster A (5 isolates) being the most common. These results show that cockroaches are important in transmitting resistance factors as mechanical vectors. Therefore, taking sanitary measures to control the insect population is unavoidable.